2013 ACC/AHA Cholesterol Guideline and Implications for Healthy People 2020 Cardiovascular Disease Prevention Goals. Issue 8 (August 2016) - Egan, Brent M.; Li, Jiexiang; White, Kellee; Fleming, Douglas O.; Connell, Kenneth; Hernandez, German T.; Jones, Daniel W.; Ferdinand, Keith C.; Sinopoli, Angelo
Abstract : Background: Healthy People 2020 aim to reduce fatal atherosclerotic cardiovascular disease (ASCVD) by 20%, which translates into 310 000 fewer events annually assuming proportional reduction in fatal and nonfatal ASCVD. We estimated preventable ASCVD events by implementing the American College of Cardiology/American Heart Association (ACC/AHA) 2013 Cholesterol Guideline in all statin‐eligible adults. Absolute risk reduction (ARR) and number needed‐to‐treat (NNT) were calculated. Methods and Results: National Health and Nutrition Examination Survey data for 2007–2012 were analyzed for adults aged 21 to 79 years and extrapolated to the US population. Literature‐guided assumptions were used including (1) low‐density lipoprotein cholesterol falls 33% with moderate‐intensity statins and 51% with high‐intensity statins; (2) for each 39 mg/dL decline in low‐density lipoprotein cholesterol, 10‐year ASCVD10 risk would fall 21% when ASCVD10 risk was ≥20% and 33% when ASCVD10 risk was <20%; and (3) either all statin‐eligible untreated adults or all with ASCVD10 risk ≥7.5% would receive statins. Of 175.9 million adults aged 21 to 79 years not taking statins, 44.8 million (25.5%) were statin eligible. Treating all statin‐eligible adults would prevent an estimated 243 589 ASCVD events annually (ARR 5.4%, 10‐year NNT 18). Treating all statin‐eligible adults with ASCVD10 risk ≥7.5% reduces the number treated to 32.2 million (28.2% fewer), whereas ASCVD events prevented annually fall only 10.5% to 217 974 (6.8% ARR, NNT 15). Conclusions: Implementing the ACC/AHA 2013 Cholesterol Guideline in all untreated, statin‐eligible adults could achieve ≈78% of the Healthy People 2020 ASCVD prevention goal. Most of the benefit is attained by individuals with 10‐year ASCVD risk ≥7.5%.